2020
DOI: 10.1016/j.expthermflusci.2020.110110
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the aluminum combustion in different O2 oxidizing mixtures: Effect of the diluent gases

Abstract: The existence of different distinct phases during the aluminum combustion process was unambiguously proved and widely discussed in several studies on single burning aluminum particles. Indeed, in the case of a combustion in diffusion vapor phase, the formation of growing aluminum oxide caps on the droplet surface is suspected to drive the transition from a symmetric to an asymmetric regime. Especially based on diverse observations for aluminum particles burning in O2/N2, a hypothesis was proposed on the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 12 publications
2
7
1
Order By: Relevance
“…We moreover assume that electrophoresis (due to electric charges) is weak, because of intense thermoionic emission at the high temperatures of smoke in the flame. This seems supported by experiments in our electrodynamic levitator [34,35,16] where no deformations of the flame due to the imposed electric field were ever observed.…”
Section: Mechanisms Of Oxide Smoke Motionsupporting
confidence: 67%
See 4 more Smart Citations
“…We moreover assume that electrophoresis (due to electric charges) is weak, because of intense thermoionic emission at the high temperatures of smoke in the flame. This seems supported by experiments in our electrodynamic levitator [34,35,16] where no deformations of the flame due to the imposed electric field were ever observed.…”
Section: Mechanisms Of Oxide Smoke Motionsupporting
confidence: 67%
“…We do believe that this "asymmetric" regime is actually just related to the rapid build-up of smoke above the lobe. This symmetric/asymmetric transition was studied recently by the present authors [16] and we found that the nature of gas is of primary importance. The fraction τ of the burning time spent in the symmetric regime is in the range 0.9∼1 (i.e., no asymmetric regime) for O 2 /He and O 2 /Ar mixtures at large dilution ratio (O 2 < 40 %).…”
Section: Effect Of the Oxide Lobe During Combustionsupporting
confidence: 53%
See 3 more Smart Citations